FANATIC TENDENCIES AMONG KIRKUK UNIVERSITY STUDENTS (American Journal of Research in Humanities and Social Sciences, 2024)
Ntolerance is a common trait that appears among many individuals, even if its forms and manifestations vary, and its effects include a person’s psychological and intellectual health, as well as his lifestyle and behavior. Which is related to the state of well-being in a person and is the result of psychological, social and political pressures that a person experiences, and is accompanied by many social, economic and psychological problems and difficulties. The concept of fanaticism has emerged as a trend that is often not based on many facts and evidence, which causes a lot of aversion, hatred, and devaluation of the status and status of other individuals and groups. It includes stereotypes that are difficult to change, even if there is evidence and facts that suggest the opposite. Given the great energy that university students represent, flowing with effectiveness and creativity, they are the pillars of the present and the guarantee of the future. All cultural transformations throughout modern history began with the youth, especially university students. Therefore, we must seek to discover this wealth and exploit them by arriving at solutions to negative phenomena and paving the way. The way to improve social conditions is through understanding phenomena and controlling themThe aim of the current research is to identifyThe level of intolerant attitudes among university students.1-2-The difference in the level of neurotic tendencies among high school students and in the specialization variable (scientific, humanitis)3-The difference in the level of neurotic tendencies among students of this stage and in the gender variable (males, females ) .The research population included Kirkuk University students, numbering (21,972). A random sample of (400) male and female students was selected. For the purpose of achieving the research objectives and fulfilling its requirements, the researcher prepared a scale to measure fanatical tendencies, presented it, and the psychometric properties of the scale were verified. Thus, the scale became ready to be applied to the research sample. For the purpose of analyzing the data and obtaining results, the researcher used a number of statistical methods, including the t-test for one sample and the t-test for two independent samples. The results resulted in the sample members having a number of neurotic tendencies and that there was no statistically significant difference in the neurotic tendencies according to the specialization variable (scientific, humanities). In light of the results, the researcher used a number of recommendations and proposals.